2014
DOI: 10.1016/j.anbehav.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Male mate preferences in mutual mate choice: finches modulate their songs across and within male–female interactions

Abstract: Male songbirds use song to advertise their attractiveness as potential mates, and the properties of those songs have a powerful influence on female mate preferences. One idea is that males may exert themselves maximally in each song performance, consistent with female evaluation and formation of mate preferences being the primary contributors to mate choice. Alternatively, males may modulate their song behaviour to different degrees in the presence of different females, consistent with both male and female mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 72 publications
2
36
0
Order By: Relevance
“…Social context affects song structure in a number of species, including the Bengalese finch (Sakata et al, ; Hampton et al, ; Sakata and Brainard, ; Dunning et al, ; Heinig et al, ). For example, relative to spontaneous, UD songs, songs directed at females during courtship interactions (FD songs) consist of syllables that are more stereotyped in structure and arranged in more stereotyped sequences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Social context affects song structure in a number of species, including the Bengalese finch (Sakata et al, ; Hampton et al, ; Sakata and Brainard, ; Dunning et al, ; Heinig et al, ). For example, relative to spontaneous, UD songs, songs directed at females during courtship interactions (FD songs) consist of syllables that are more stereotyped in structure and arranged in more stereotyped sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Just as syllable structure is less variable during FD song than UD song, the sequencing of syllables at branch points is less variable when Bengalese finches produce FD song than UD song (Sakata et al, ; Hampton et al, ; Sakata and Brainard, ; Heinig et al, ). Consistent with previous data, we found that syllable sequencing was less variable when FD birds produced FD song on the experimental day than UD song on the control day.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies focusing on courtship dynamics have acknowledged the interactive nature of the behaviors that precede mate choice (Medina, Garcia, Urbina, Manjarrez, & Moyaho, ; Yoshikawa, Ohkubo, Karino, & Hasegawa, ). In a mutual mate choice scenario, both males and females exhibit courtship displays to advertise individual quality (Tobias, Viswanathan, & Kelley, ; Heinig et al., ); thus, partner assessment is a reciprocal process, such that both sexes process information on the quality of a mate. This can occur even in scenarios of unequal investment between the sexes, as in many frogs where females invest more in reproduction and are therefore thought of as the choosy sex.…”
Section: Discussionmentioning
confidence: 99%